MAKNA FURUSATO DALAM DUA LIRIK LAGU BERJUDUL FURUSATO KARYA ANGELA AKI DAN KOYAMA KUNDO - Cok Istri, vera Kumayastuti (Humanis, 2015)
Furusato describes the Japanese traditional culture. Furusato is also a concept of the Japanese people's minds to describe the beauty of the countryside nature in Japan. This study discusses the meaning of furusato in two song entitled Furusato and the message contained in the lyrics of those songs. This research using descriptive analysis and dialectical techniques as methods and techniques of data analysis. The theory used in this study is a semiotic theory and intertextual theory propounded by Riffaterre. Based on the analysis, the meaning of furusato in the lyrics of Angela Aki's song are the birthplace, home, and a place for the family to gather together. Meanwhile, the Furusato's meaning in the lyrics of Koyama Kundo's song are the birthplace, home, place of work and a place to study for the victims of the earthquake and tsunami in the Tohoku region. The message contained in this two songs are: 1) to keep and protect the cleaness of the environment; 2) to remember and never forget the hometown; 3) to try hard and don’t give up for achieve the goals; 4) to grateful the people who have helped us; 5) to help each other when in trouble; 6) to be strong and don’t give up to overcome any problem; and 7) to protect the future of our children.
Keywords: furusato, semiotics Riffaterre, intertextual